Perbandingan Kemampuan Aerasi Sembur (Spray) dengan Metode Adsorpsi Menggunakan Adsorben Serbuk Kulit Buah Kakao untuk Menurunkan Kadar Besi dan Mangan Pada Air Sumur Gali - Harimu, La; Haetami, Aceng; Sari, Citra Purnama; Haeruddin, Haeruddin; Nurlansi, Nurlansi (Indonesian Journal of Chemical Research, 2020)
Research on the use of the spray aeration method with adsorption of cocoa rind powder to reduce iron and manganese levels in dug well water has been carried out. This study aims to make comparisons from two methods to reduce iron and manganese in dug well water. The parameters optimized in this study are the aeration time and the variation of the addition of the adsorbent mass and the adsorption time. Based on the research results, the spray aeration time for 2 hours gave the optimal percentage reduction for Fe3+ and Mn4+ metal ions, namely 98.68% and 94.22%. Meanwhile, for adsorption using cocoa pod husk powder, the optimal reduction occurred in the adsorbent mass of 0.2 grams and the adsorption time of 60 minutes for iron and manganese 96.36% and 95.15%, respectively.